(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Programs that utilize the finite element method (FEM) have as purpose the virtual analysis of real problems, and there is a search for those with better results reliability at lower cost. Hence, the comparison between free and proprietary FEM platforms was proposed, using data from an experimental test to feed the analysis and compare it with the numerical results. It has been noted that in the studied point the variations in relation to experimental data were below 15% and under 6% in comparison to analytical data. Consequently, as to the accuracy of static analysis results, it was possible to verify that free programs have similar reliability as proprietary ones.